Dampak Brand Image, Fashion Lifestyle Dan Harga Terhadap Keputusan Pembelian Pakaian Branded Preloved Di Online Shop - Ambardi, Ambardi; Aini, Nur; Husnayeti, Husnayeti; Helmi, Helmi (Politeknik Negeri Ambon, 2023)
The purpose of this study is to find out and analyze the impact of Brand Image, Fashion Lifestyle, nd Price on Purchase Decisions for Branded Preloved Clothing in the Online Shop. This research uses descriptive qualitative and quantitative methods. Determination of the sample using certain criteria, namely respondents who follow the Instagram account @Latacha.Thriftshop and have bought preloved branded clothes at thriftshop @Latacha.Thriftshop at least 1 time. The sampling technique in this research uses a non-probability sampling technique using a purposive sampling method. Then the questionnaire was assessed using a Likert scale which was given a score of 1-5 for each question item, then the Instrument Test and Classical Assumption Test were carried out as well as Multiple Linear Regression Analysis and hypothesis testing. The results of this study conclude that the brand image variable has a significant effect on preloved purchasing decisions in online shops. The next variable price also has a significant effect on the purchase decision variable of Preloved onlineshop. And lastly, the Fashion Lifestyle variable also has a significant effect on preloved purchasing decisions in online shops